Dynamics of Students’ Social Interaction in a Multicultural School Environment: A Case Study of SDN 4 Kamalu - Ervina J. Gani; Hasia Marto; Muh. Khaerul Ummah BK (Madako Elementary School, 2026)
The central phenomenon of this study is the suboptimal social interaction among students from diverse cultural and religious backgrounds in multicultural elementary schools, which may lead to both cooperation and conflict. This study aims to describe forms of social interaction, identify influencing factors, and examine the roles of teachers and schools in fostering harmony at SDN 4 Kamalu. The participants include the principal, teachers, and student representatives from various ethnic and religious groups. A descriptive qualitative approach was applied, with data collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and triangulation-based conclusion drawing. The findings reveal that interactions occur in both associative and dissociative forms. Associative interactions are reflected in cooperation, tolerance, and mutual assistance, while dissociative interactions appear as competition and minor conflicts. Influencing factors include imitation, suggestion, identification, sympathy, empathy, cultural diversity, communication patterns, and the school environment. Teachers and schools play a strategic role by fostering values of tolerance and respect for diversity. These findings highlight the potential of multicultural elementary schools in promoting tolerance and social cohesion through inclusive pedagogical practices and sustainable policies.  The strengthening of inclusive pedagogical practices and school policies constitutes the final recommendation of this study.